The Effect of the Tourism Sector on Economic Growth in Indonesia - Akmalina, Anida; Retno Febriyastuti Widyawati, (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to analyze the effect of the tourism sector on economic growth in Indonesia using the variables of Foreign Direct Investment (FDI), foreign tourists, and travel services. The data used covers the period 2008-2022 with quantitative methods and descriptive approaches. Multiple linear regression tests were used to test the effect of these variables on Gross Domestic Product (GDP). The results show that FDI has no significant influence on GDP, with a negative relationship between the two variables. In contrast, foreign tourists have an influence on GDP and travel services have a significant effect, but with a negative relationship, which may be due to external factors such as the Covid-19 pandemic. Simultaneously, the three variables affect GDP, with a contribution of 63.88%. These results confirm the importance of the tourism sector, especially foreign tourists, in driving economic growth in Indonesia.